2022
DOI: 10.1038/s41598-022-14183-0
|View full text |Cite
|
Sign up to set email alerts
|

Both cis and trans-acting genetic factors drive somatic instability in female carriers of the FMR1 premutation

Abstract: The fragile X mental retardation (FMR1) gene contains an expansion-prone CGG repeat within its 5′ UTR. Alleles with 55–200 repeats are known as premutation (PM) alleles and confer risk for one or more of the FMR1 premutation (PM) disorders that include Fragile X-associated Tremor/Ataxia Syndrome (FXTAS), Fragile X-associated Primary Ovarian Insufficiency (FXPOI), and Fragile X-Associated Neuropsychiatric Disorders (FXAND). PM alleles expand on intergenerational transmission, with the children of PM mothers bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 56 publications
1
20
0
Order By: Relevance
“…Instability of the FMR1 premutation allele has recently been described for the first time by our group on a large sample of female PM 18 . Specifically, we characterized the presence of a series of unstable expanded alleles in ~ 94% of peripheral blood samples differing from the major premutation allele by one or more repeat units.…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…Instability of the FMR1 premutation allele has recently been described for the first time by our group on a large sample of female PM 18 . Specifically, we characterized the presence of a series of unstable expanded alleles in ~ 94% of peripheral blood samples differing from the major premutation allele by one or more repeat units.…”
Section: Introductionmentioning
confidence: 59%
“…The expanded peak with the highest relative fluorescence units (RFU) value was selected as Peak 2. Expansion was calculated using the formula (Peak 2–Peak 1), more details can be found in Hwang et al 18 . Total RNA was isolated from 2.5 ml of peripheral blood collected in PAXgene (Qiagen, Valencia, CA, United States) and quantified using the Agilent 2100 Bioanalyzer system.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While expansions and, to a lesser degree, contractions, occur in any allele class, PM alleles are particularly meiotically unstable, often expanding into FM alleles in a single generation [ 40 , 42 ]. More recently, it has been shown that somatic mosaicism is also common in PM alleles and that genes involved in DNA repair may play a role in somatic expansion risk, as reported in other repeat-expansion disorders [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, studies in RED patient cohorts using genome-wide association (GWA) or the testing of candidate MMR gene polymorphisms suggest that functional MMR components are required for some, if not all, STR expansions that cause the REDs (Refs 69 74 ). This is consistent with evidence from mouse and human cell models of a number of these disorders that shows a requirement for MutS β and MutL γ (reviewed in Ref.…”
Section: Msi In the Redsmentioning
confidence: 99%